If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 2t = 1 Solving -4 + 2t = 1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2t = 1 + 4 Combine like terms: -4 + 4 = 0 0 + 2t = 1 + 4 2t = 1 + 4 Combine like terms: 1 + 4 = 5 2t = 5 Divide each side by '2'. t = 2.5 Simplifying t = 2.5
| 58=3a+10 | | 5-2*x=19 | | 8y+23=33 | | 3x+1=-7-5x | | 533.71=40y+2.5y | | y=40y+2.5y | | 2y-2x+6=0 | | 9-1=t+(-19) | | 3(2x+3)=x+24 | | an=2n^2-5 | | 7-2*x=15 | | 6x(5x+5)=-2 | | X^2+28x+1040=0 | | -2(-x^2-12)=-2x^2-12 | | 8x+10=6x+14 | | 7(x^2+5)=42 | | 25x^2-170x+289=54 | | x^2+2x^2+x=0 | | ln(x^2+5)=x^43+9x+199 | | 7-3ln(x)=2 | | 2ln(x+2)=8 | | x+125=8436734987 | | Ln(3*x)=20 | | a+5=5-5a+5 | | log(2x+6)=0 | | x^2+y^2+2x+2y+2=0 | | X^2-6x+5=13 | | 6-7(9+1)=3(2-9) | | 8p-7=5+2p | | 7-3lnx=2 | | 4x^2-kx+25=0 | | -119=4x-11 |